THE ROLE OF INNOVATION IN GLOBALIZATION AND THE DIGITAL ECONOMY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article discusses the role and importance of innovation in the context of globalization and the digital economy. The influence of instantaneous information on the country's economy, their throughput and the level of efficiency for users are discussed.